Hotel and Restaurant Management System Core Transaction 1 (Order Management W/POS, Kitchen and Bar Module, Food and Beverage Costing, Inventory Management, Resto Analytics): Vol.3, No.1B (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Restaurants have been transformed by the wave of technological applications produced by information technology. The Core 1 system of Hotel and Restaurant Management refers to actions. Users must complete tasks on this platform to exchange value, which is the foundation of any platform business. Hotel and restaurant management systems provide the correct information at the right time, leading to fewer costly mistakes, better forecasting, and higher productivity. The applications covered in this chapter include inventory management systems, order processing with POS systems for table service, food and beverage costing for menu management, kitchen and bar management, and restaurant analytics transaction processes in the information technology field.Through agile methodology, the development team conducted internet research. After planning, the Project Team began designing the website, where requirements and solutions evolved through user collaboration. The development team researched and created reports to engage in the project's development. I also maintain the system to prevent defects. Deployment is another step in improving the scenario by providing feedback.The POS Order system is commonly utilized in restaurants to handle sales and includes hardware components like computers to manage the process.The most basic function of POS is to handle sales. The Kitchen and Bar Management Modules manage the production order regarding the number of items or recipes and generate the average lead time for work-in-process goods and finished products. The food and beverage costing management inputs the ingredients of the product's recipes and calculates the cost into the menu. The Inventory Management System refers to the system processes that manage the restaurant's stocks. Lastly, the Restaurant Analytics Management System is a system that reports on different sub-modules to analyze how the restaurant manages its everyday development or improvement.With the industry's increasing competition, it is more important than ever for a hotel or restaurant to provide quality service to their guests by upgrading the core transaction, which includes order management with POS, kitchen and bar procedures, food and beverage costing, inventory management, and Resto analytics. This unique approach can help achieve its goals.